An Atypical Presentation of Pyridoxine-Dependent Epilepsy Diagnosed with Whole Exome Sequencing and Treated with Lysine Restriction and Supplementation with Arginine and Pyridoxine - Jiyoung Kim; Angela Pipitone Dempsey; Sun Young Kim; Meral Gunay-Aygun; Hilary J. Vernon (Case Reports in Genetics)
Pyridoxine dependent-developmental and epileptic encephalopathy (PD-DEE) or pyridoxine-dependent epilepsy (PDE) is a rare autosomal recessive disorder caused by biallelic pathogenic variants in ALDH7A1. It classically presents as intractable infantile-onset seizures unresponsive to multiple antiepileptic drugs (AEDs) but with a profound response to large doses of pyridoxine (B6). We report a case of PDE with an atypical clinical presentation. The patient presented at 3 days of life with multifocal seizures, fever, increased work of breathing, decreased left ventricular systolic function, and lactic acidosis, raising suspicion for a mitochondrial disorder or infectious process. Within 1.5 weeks of presentation, seizure activity resolved with antiepileptic therapy. Whole exome sequencing (WES) revealed homozygous pathogenic variants in ALDH7A1 (c.1279G > C, p.E427Q) and confirmed the diagnosis of PDE. Follow-up biochemical testing demonstrated elevated urine pipecolic acid. In the second week of life, the patient was initiated on triple therapy, including pyridoxine supplementation, low lysine diet, and arginine supplementation, which he tolerated well. Urine pipecolic acid levels responded accordingly after initiation of therapy. Our case illustrates the diagnostic challenges in PDE, the utility of rapid WES in such cases, and the response in urine pipecolic acid to therapy.